KETIMPANGAN DUKUNGAN DALAM PENDIDIKAN: KETERBATASAN EKONOMI, TEKNOLOGI DAN KESIAPAN SISWA DI SDN SUNGAI MIAI 8 BANJARMASIN - Nazwa Aprina; Maulida Irmayanti; Herliani; Khusnul Hatimah; Diani Ayu Pratiwi; Aslamiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the disparities in educational support at SDN Sungai Miai 8 Banjarmasin. The main focus is on economic limitations, access to technology, and students’ readiness to participate in the learning process. These disparities pose significant barriers to achieving equitable and quality education for all. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with teachers, students, and parents to identify the main challenges faced. The findings reveal that most students come from low-income families, which limits access to adequate learning facilities at home, such as technological devices and internet connectivity. Furthermore, students’ ability to engage in technology-based learning remains low, especially since the implementation of the Merdeka Curriculum, which demands greater independence and creativity. Teachers strive to adapt their teaching methods to better suit students’ conditions but are still constrained by limited resources and support. Therefore, strong collaboration between schools, parents, and the government is essential to ensure that every student has equal opportunities to receive a proper education, regardless of economic or technological barriers.